#### Answer

y=1

#### Work Step by Step

Simplifying
13y + 2 = 20y + -5
Reorder the terms:
2 + 13y = 20y + -5
Reorder the terms:
2 + 13y = -5 + 20y
Solving
2 + 13y = -5 + 20y
Solving for variable 'y'.
Move all terms containing y to the left, all other terms to the right.
Add '-20y' to each side of the equation.
2 + 13y + -20y = -5 + 20y + -20y
Combine like terms: 13y + -20y = -7y
2 + -7y = -5 + 20y + -20y
Combine like terms: 20y + -20y = 0
2 + -7y = -5 + 0
2 + -7y = -5
Add '-2' to each side of the equation.
2 + -2 + -7y = -5 + -2
Combine like terms: 2 + -2 = 0
0 + -7y = -5 + -2
-7y = -5 + -2
Combine like terms: -5 + -2 = -7
-7y = -7
Divide each side by '-7'.
y = 1
Simplifying
y = 1